2012
DOI: 10.1063/1.3672035
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of lipid vesicle with silver nanoparticle-serum albumin protein corona

Abstract: The physical interaction between a lipid vesicle and a silver nanoparticle (AgNP)-human serum albumin (HSA) protein "corona" has been examined. Specifically, the binding of AgNPs and HSA was analyzed by spectrophotometry, and the induced conformational changes of the HSA were inferred from circular dichroism spectroscopy. The fluidity of the vesicle, a model system for mimicking cell membrane, was found to increase with the increased exposure to AgNP-HSA corona, though less pronounced compared to that induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
50
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 33 publications
(30 reference statements)
4
50
0
Order By: Relevance
“…In our case, the interaction of Ag NPs with BSA molecules resulted in a further change of e which resulted in a redshift of the extinction coefficient maximum, and the observed redshift in the SPR peaks. 17 Interestingly, Fig. 2(d) showed that the amount of redshift is dependent on the nature of surface groups present on the Ag NPs.…”
mentioning
confidence: 96%
“…In our case, the interaction of Ag NPs with BSA molecules resulted in a further change of e which resulted in a redshift of the extinction coefficient maximum, and the observed redshift in the SPR peaks. 17 Interestingly, Fig. 2(d) showed that the amount of redshift is dependent on the nature of surface groups present on the Ag NPs.…”
mentioning
confidence: 96%
“…20 Third, changes in local membrane curvature followed by wrapping of NPs and their agglomerates may lead to lipid depletion from the bilayer, and thus altered membrane integrity and/ or formation of pores or holes. 16,22,[53][54][55][56][61][62][63][64] In the case of GUVs, we propose that the most likely mechanism causing GUVs to burst is adhesion of CAadsorbed CoFe 2 O 4 NPs and smaller NP agglomerates onto membranes, resulting in alteration of the global membrane curvature and, finally, bursting. The POPC lipids used in our study have an externally situated lipid polar head (the trimethylammonium group) that is positively charged and faces the aqueous glucose solution.…”
Section: Mlvs After Incubation In Np Suspensionsmentioning
confidence: 99%
“…11,12 Experimental, computational, and theoretical studies suggest that the NP-lipid interaction at the membrane can compromise the structure and function of both artificial and biological membranes. 1,[12][13][14][15][16] NPs and their agglomerates can be adsorbed onto the membrane and cause its structural reorganization, [13][14][15][16] leading to changes in membrane curvature, [17][18][19] particle internalization, 20 and pore and hole formation. 21,22 The interactions between lipid bilayers and solid surfaces are complex and can involve van der Waals, electrostatic, hydration, hydrophobic, or protrusion forces.…”
Section: Introductionmentioning
confidence: 99%
“…Among the diverse silver containing drugs that are currently used in medicine, viz., solutions, oint ments, alloys (lapis), colloidal silver, and nanoparti cles with different coats, the effect of the last form, which appeared only recently, has been studied most extensively. The available published data are sufficient to notice a significant difference in the membranotro pic effect of ionic and dispersed silver forms: the former is reported to have a tightening effect on the bilayer, whereas the latter causes its fluidization [13][14][15][16]. It was also shown that silver nanoparticles accu mulate in the cell wall and inside the cell [3,17,18].…”
Section: Introductionmentioning
confidence: 94%